Highly conductive nanocellulose–polyaniline nanocomposites for efficient heavy metal adsorption and regeneration - Abdullah, Nur Athirah; Rani, Mohd Saiful Asmal; Mohammad, Masita; Ramlee, Muhamad Fadhli; Ilyas, Rushdan Ahmad (Taylor and Francis, 2026)
Polyaniline (PANI) is extensively researched for its conductivity and enhanced properties for multifunctional commercial applications, addressing heavy metal pollution. This work details the synthesis of nanocellulose/copper ions (NCs-Cu2+) doped PANI nanocomposites via in-situ polymerization which assesses the nanocomposites’ efficiency in heavy metal adsorption and their regenerability. NC extraction employs acid hydrolysis, while batch adsorption experiments consider parameters like pH, adsorbent dosage, Cu2+ concentration, and contact time. Nanocomposites are prepared using different ratios to compare conductivity (1:9, 2:8, 3:7) and characterized using XRD, FESEM, TEM, FTIR, and TGA. XRD reveals increased ordering with NC-Cu2+ concentration, indicating a highly ordered PANI structure in the presence of NC-Cu2+. FESEM shows morphological changes and homogenous nano dispersion. TEM depicts rod-like NC-Cu2+ PANI structures. FTIR demonstrates slight peak shifts during in-situ polymerization and TGA confirms its high thermal stability. Adsorption mechanisms are studied with Langmuir and Freundlich isotherms, showing good agreement between experimental and theoretical data. The conductivity of NC-Cu2+PANI ranges from 5.73 to 18.27 × 10 S/cm−1, significantly higher than pure PANI (3.53 × 10 S/cm−1), with a decrease in conductivity as the NC-Cu2+-to-PANI ratio increases. This research provides insights into the synthesis, properties, and applications of PANI-based nanocomposites for heavy metal removal.